Ethnomathematics in the Digitalization of Museums in Indonesia by Using Virtual Reality - Sri Adi Widodo; Siti Muslikhatul Tsaniyah; Lisnani Lisnani (Universitas Negeri Surabaya, 2025)
This research explores the integration of ethnomathematics and virtual reality (VR) to digitize Indonesian museums, enhancing educational accessibility and cultural preservation. The study aims to investigate how VR technology can visualize and communicate mathematical knowledge embedded in Indonesian cultural artifacts, particularly within traditional crafts, architecture, and measurement systems. Employing a qualitative approach with a design-based research (DBR) methodology, data were gathered through observation, interviews, and artifact analysis in several Indonesian museums. VR-based ethnomathematics models were developed, tested, and revised iteratively. Findings show that VR facilitates immersive experiences and improves student engagement in learning mathematics through cultural context. This approach contributes to mathematics education by integrating technology and local culture within the framework of ethnomathematics. Integrating ethnomathematics and virtual reality (VR) in museum digitalization has significant implications for mathematics education research. VR-based applications in ethnomathematics offer inclusive opportunities for students in remote or underserved areas to experience museum-based learning. This addresses educational equity and access, especially for regions where physical museum visits are not feasible.